PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 RANAH PESISIR - Saputra, Andri; Aima, Zulfitri; Pratiwi, Merina (Pendidikan Matematika, 2013)
This research was conducted based on the phenomena indicating that the teachers did not seem to have their students study in a group and were not likely to challenge them in the form of group competition. Therefore, the students were not willing to share what they have already learned with others and this condition made their understanding on mathematical concept became unsatisfactory. This could be seen from the learning achievement of the first year students of SMPN 4 Ranah Pesisir in math in Academic Year 2012/2013. This research was aimed at revealing the use of Learning Tournament active learning strategy gave better effect on the studentsâ understanding on mathematical concept than that of conventional learning strategy in class VIII of SMPN 4 Ranah Pesisir in Academic Year 2013/2014. This was an experimental research which used random research design toward the subject. The population of the research was all of students in class VIII of SMPN 4 Ranah Pesisir in Academic Year 2013/2014 which was divided into two classes. By using random sampling technique, class VIII2 was chosen as the experimental class and class VIII1 was as the control class. The instrument of the research was an essay post-test whose reliability was 0.83. The result of data analysis showed that p-value < Î±, thus the hypothesis was accepted. In conclusion, the use of Learning Tournament active learning strategy improved the studentsâ understanding on mathematical concept better than that of conventional learning strategy.